2021
DOI: 10.1002/advs.202102886
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of CO2 to CO over Transition Metal/N‐Doped Carbon Catalysts: The Active Sites and Reaction Mechanism

Abstract: Electrochemical CO2 reduction to value‐added chemicals/fuels provides a promising way to mitigate CO2 emission and alleviate energy shortage. CO2‐to‐CO conversion involves only two‐electron/proton transfer and thus is kinetically fast. Among the various developed CO2‐to‐CO reduction electrocatalysts, transition metal/N‐doped carbon (M‐N‐C) catalysts are attractive due to their low cost and high activity. In this work, recent progress on the development of M‐N‐C catalysts for electrochemical CO2‐to‐CO conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 129 publications
(279 reference statements)
2
89
0
Order By: Relevance
“…[ 9 , 10 , 11 , 12 , 13 , 14 ] Codoping with multiple heteroatoms to alter the electronic structure of the active sites is also one of the most effective ways to improve the catalytic activity of metal‐free materials. [ 15 , 16 , 17 ] These findings provide important insights into the relationship between catalytic activity and electronic structures. However, the synergistic modulation of codopants and the corresponding active sites involved in the catalytic reaction remains challenging, which impacts the rational design of high‐performance metal‐free catalysts in this burgeoning research area.…”
Section: Introductionmentioning
confidence: 96%
“…[ 9 , 10 , 11 , 12 , 13 , 14 ] Codoping with multiple heteroatoms to alter the electronic structure of the active sites is also one of the most effective ways to improve the catalytic activity of metal‐free materials. [ 15 , 16 , 17 ] These findings provide important insights into the relationship between catalytic activity and electronic structures. However, the synergistic modulation of codopants and the corresponding active sites involved in the catalytic reaction remains challenging, which impacts the rational design of high‐performance metal‐free catalysts in this burgeoning research area.…”
Section: Introductionmentioning
confidence: 96%
“…Excessive emission of carbon dioxide has made the concentration of CO 2 in the atmosphere increase year by year, resulting in an increasingly serious greenhouse effect, and posing a serious threat to the ecological environment. [1][2][3][4][5] Converting excess CO 2 into high value-added chemicals is an effective strategy to achieve carbon neutrality and alleviate energy shortages. In recent years, the electrochemical reduction of CO 2 has gradually become a research hotspot for its controllable reaction and simple operation.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Recently, single-atom catalysts (SAC) have attracted attention due to their high atom utilization and excellent catalytic performance. 2,10,[18][19][20][21] Studies have shown that the dualmetal-nitrogen-carbon materials exhibit high catalytic activity in CO 2 RR due to the synergistic effect of the bimetallic centers. [22][23][24][25][26] Ren et al 22 prepared a Ni/Fe-N-C catalyst with isolated diatomic Ni-Fe sites.…”
Section: Introductionmentioning
confidence: 99%
“…Product selectivity, low Faradaic efficiencies, and the high overpotentials required to drive the reaction are the major drawbacks of electrochemical CO 2 reduction. Methods to mitigate these issues include controlling catalyst size and morphology, crystal structure, pH, and other reaction conditions. The use of mixed metals is another approach to tune the selectivity of CO 2 reduction catalysts. Alloys afford the opportunity to modulate the surface properties of electrocatalysts to optimize their selectivity and catalytic activity. For example, Cu–Sn and Cu–Zn catalysts have been shown to be selective for either CO or HCOOH. , Stojkovikj et al used a H 2 -assisted electrodeposition method to fabricate a porous Cu–Sn bronze electrocatalyst capable of achieving >85% CO Faradaic efficiency while suppressing the thermodynamically favored H 2 evolution reaction (HER) .…”
Section: Introductionmentioning
confidence: 99%